Privatization of Education in India: A Critical View - Datta, Lusika; Kundu De, Usashi (International Journal of Social Sciences and Management, 2021)
Privatization is considered a process which is defined as the transfer of shares or assets, management, responsibilities from the public to private sector. Today it becomes a major issue in Education system. The present paper traces supportive decisions taken by India Government favouring privatization of Education. It also seeks to analyse the present condition of higher education with special reference to privatization of education in India. The paper follows analytical description as methodology through secondary data. It points out the emergence of private sector in higher education. Positive and negative impact of privatization on education & society are also identified. Int. J. Soc. Sc. Manage. Vol. 8, Issue-2: 352-358